CHI '09 Extended Abstracts on Human Factors in Computing Systems 2009
DOI: 10.1145/1520340.1520742
|View full text |Cite
|
Sign up to set email alerts
|

Best practices in longitudinal research

Abstract: This workshop will identify best practices for longitudinal research through an in-depth exploration of methods and metrics for collecting and analyzing user data over time. This is the fourth event in an ongoing effort by the organizers to enhance our current body of knowledge about longitudinal research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 3 publications
(2 reference statements)
0
14
0
3
Order By: Relevance
“…As this study is based on an initial investigation of product requirements, Hassenzahl's (2003) model was considered to be the most suitable for the purpose of this study. While Vermeeren et al (2010) suggested exploring early design features in the early development stage in order to get feedback on new products, it was argued that studying the change of user experience over time was becoming increasingly important (Courage et al, 2009). Particularly for creating customer loyalty, it was not considered sufficient to rely on early study results, but long-term studies were necessary.…”
Section: Literature Review 21 User Experiencementioning
confidence: 99%
“…As this study is based on an initial investigation of product requirements, Hassenzahl's (2003) model was considered to be the most suitable for the purpose of this study. While Vermeeren et al (2010) suggested exploring early design features in the early development stage in order to get feedback on new products, it was argued that studying the change of user experience over time was becoming increasingly important (Courage et al, 2009). Particularly for creating customer loyalty, it was not considered sufficient to rely on early study results, but long-term studies were necessary.…”
Section: Literature Review 21 User Experiencementioning
confidence: 99%
“…Many UX models have been proposed during the past decade (Desmet and Hekkert [3]; Forlizzi and Battarbee [6]; Hassenzahl and Tractinsky [8]; Hassenzahl [9]; Jordan [13]). Moreover, in the context of longterm UX, there are a few published research studies (Courage et al [2]; Hassenzahl et al [10]; Karapanos et al [15,16,17]; Kujala et al [20]; Mahlke [23]; Tractinsky and Zmiri [27]; Von Moellendorff et al [30]). …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In some studies (Hassenzahl et al [10]; Mahlke [23]; Tractinsky and Zmiri [27]) the investigation was performed in short test tasks. In one study (Courage et al [2]), the researcher investigated five weeks of usage. On the other hand, in studies such as Von Moellendorff et al [30] and Karapanos et al [15,16,17], researchers investigated the evolving nature of UX over months.…”
Section: Long-term User Experience and Its Importancementioning
confidence: 99%
“…Then, to provide a better venue for in-depth discussion, we conducted a workshop at CHI 2009 [3], where participants discussed the open issues raised at the SIG and panel.…”
Section: Previous Related Work Leading To This Workhopmentioning
confidence: 99%
“…Prior to the CHI 2009 workshop, the authors also conducted a workshop at the 2008 Usability Professionals' Association conference [3]. We generated alternative definitions of "longitudinal research," prioritized over 30 questions of interest, and began developing best practices.…”
Section: Previous Related Work Leading To This Workhopmentioning
confidence: 99%